Law Enforcement Against the Distribution of Pirated Digital Books Under Law No. 28 of 2014 on Copyright - Livia Fajarisalfa; Dewi Mayang Arum; Ikhwan Aulia Fatahillah (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The rapid expansion of digital technology has transformed the circulation of literary works, particularly electronic books, while simultaneously intensifying copyright infringement through unauthorized digital reproduction and distribution across online platforms, electronic marketplaces, and decentralized cyber networks. This study examines the legal construction, enforcement mechanisms, and structural obstacles concerning the circulation of pirated digital books under Law Number 28 of 2014 concerning Copyright within Indonesia’s contemporary digital ecosystem. Employing normative-juridical legal research, the study applies statutory, conceptual, and doctrinal approaches through qualitative analysis of legislation, legal doctrines, scholarly literature, and relevant regulatory frameworks governing copyright and electronic systems. The analysis demonstrates that Indonesian copyright law formally provides comprehensive protection for digital books through civil, criminal, and administrative enforcement mechanisms, yet operational effectiveness remains constrained by complaint-based criminal procedures, fragmented intermediary liability standards, technological enforcement limitations, and the normalization of digital piracy within online culture. The study further argues that effective copyright protection in cyberspace requires an integrated cyber-regulatory framework emphasizing preventive governance, intermediary accountability, technological supervision, and strengthened legal consciousness to ensure sustainable protection of intellectual property rights within digitally mediated environments.